2016
DOI: 10.1007/978-3-319-42023-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Niches and Sanctuaries: A Route to Acquired Resistance

Abstract: A tumor vasculature that is functionally abnormal results in irregular gradients of metabolites and drugs within the tumor tissue. Recently, significant efforts have been committed to experimentally examine how cellular response to anti-cancer treatments varies based on the environment in which the cells are grown. In vitro studies point to specific conditions in which tumor cells can remain dormant and survive the treatment. In vivo results suggest that cells can escape the effects of drug therapy in tissue r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 68 publications
2
30
0
Order By: Relevance
“…They showed that resistance arises first in cells located in regions with poor drug penetration, named pharmacological sanctuaries, and then populate areas with higher drug levels. Our own research showed that the non-homogeneous drug distribution within the tumor tissue that results in emergence of tissue regions with poor drug penetration but with normal oxygenation levels may lead to the emergence of acquired resistance (13,14). Similar results were previously generated using different mathematical models.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…They showed that resistance arises first in cells located in regions with poor drug penetration, named pharmacological sanctuaries, and then populate areas with higher drug levels. Our own research showed that the non-homogeneous drug distribution within the tumor tissue that results in emergence of tissue regions with poor drug penetration but with normal oxygenation levels may lead to the emergence of acquired resistance (13,14). Similar results were previously generated using different mathematical models.…”
Section: Introductionsupporting
confidence: 73%
“…However, this drug-induced damage can be counterbalanced by cell natural ability for damage repair at rate ! (three times faster that damage rate, (13,14)):…”
Section: Cell Resistance Mechanismmentioning
confidence: 97%
See 2 more Smart Citations
“…The microPKPD models, including Organoid3D, are based on the coupled reaction-diffusion equations of drug and nutrient kinetics [7,8,10], and the particle-spring model for cell mechanics [9,11].…”
Section: Quick Guide To Mathematical Methodsmentioning
confidence: 99%